Analisis Peran Pasar Uang dalam Mendukung Stabilitas Sistem Keuangan di Indonesia - Fitria Yulianti; Nur Amanatun Hosiah; Felisa Rachma Fadilla; M. Yusuf Bahtiar (Indonesia Economic Journal, 2026)
The money market is an essential component of the financial system that plays a significant role in short-term liquidity management and the implementation of monetary policy. An efficient and liquid money market is considered a crucial factor in maintaining the stability of a country’s financial system. This study aims to analyze the role of the money market in supporting financial system stability in Indonesia and to identify the mechanisms that influence the effectiveness of this role. This research employs a qualitative approach using a literature study method based on various scientific publications, financial institution reports, and policy documents relevant to the research topic. The data used are secondary data obtained from academic journals, textbooks, and official publications from financial institutions such as Bank Indonesia and Otoritas Jasa Keuangan. Data analysis was conducted using a qualitative descriptive analysis by examining theories and previous research findings related to the money market and financial system stability. The results indicate that the money market plays a strategic role in maintaining financial system stability through banking liquidity management, supporting the transmission of monetary policy, and improving the efficiency of fund distribution within the financial system. Therefore, the development of a deeper, more transparent, and integrated money market is an important factor in strengthening financial system stability in Indonesia.